THE FUTURE OF ELECTRONIC LEXICONS IN THE TRANSLATION OF ARABIC - Taufiqurrahman, H. R (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Modern technology continues to evolve and enter into all aspects of human life, including in the teaching of Arabic and its translation between people. In the past, translating a language into another language requires a good dictionary or a reliable translator. Now, dictionaries and translators can be replaced by products of technology. Therefore, electronic dictionaries based on the computer operating system or website pages of the international network or software based on mobile or smartphone. Finally, Google released "Pixel Buds" (Real-Time Translation), which translates speech to speech from different languages. It is clear, that this technological output will change the methods of education and language communication, as well as will change the patterns of Arabic dictionaries. This article provides a detailed account of the paradigm shift from the use of the printed dictionary to the digital dictionary, and from verbal communication to communication with technology tools .